Original Research: Diametric effects of hypoxia on pathophysiology of sickle cell disease in a murine model. Issue 7 (April 2016) - Tan, Fang; Ghosh, Samit; Mosunjac, Mario; Manci, Elizabeth; Ofori-Acquah, Solomon Fiifi
Hypoxia causes erythrocyte sickling in vitro ; however, its role in the pathophysiology of sickle cell disease is poorly understood. We report that hypoxia rapidly decreased oxygen saturation in transgenic sickle cell disease mice, but this effect was immediately buffered by a robust ventilatory response. The initial hypoxemia improved steadily throughout the duration of hypoxia without any detectable acute pulmonary adverse effect. Furthermore, the mice suffered acute anemia that ironically was associated with lowering of both plasma hemoglobin and heme. These results were corroborated by increased plasma haptoglobin and hemopexin levels. Markers of ischemic tissue injury increased spatiotemporally following repeated hypoxia exposures. This variation was supported by organ-specific induction of hypoxia-responsive genes. Our results show that hypoxia exerts diametric effects on sickle cell disease by promoting ischemic injury while enhancing the expression of hemolysis scavenger molecules. This phenomenon may help to understand the disparate clinical syndromes associated with hemolysis and vaso-occlusion in sickle cell disease.